Readability of Trauma-Related Patient Education Materials From the American Academy of Orthopaedic Surgeons - Eltorai, Adam E. M. (Trauma Mon, 2016)
CONTEXT: According to the american medical association (AMA) and the national institutes of health (NIH), the recommended readability of patient education materials should be no greater than a sixth-grade reading level. The online patient education information produced by the american academy of orthopaedic surgeons (AAOS) may be too complicated for some patients to understand. This study evaluated whether the AAOS’s online trauma-related patient education materials meet recommended readability guidelines for medical information. EVIDENCE ACQUISITION: Ninety-nine articles from the “Broken Bones and Injuries” section of the AAOS-produced patient education website, orthoinfo.org, were analyzed for grade level readability using the Flesch-Kincaid formula, a widely-used and validated tool to evaluate the text reading level. Results for each webpage were compared to the AMA/NIH recommended sixth-grade reading level and the average reading level of U.S. adults (eighth-grade). RESULTS: The mean (SD) grade level readability for all patient education articles was 8.8 (1.1). All but three of the articles had a readability score above the sixth-grade level. The readability of the articles exceeded this level by an average of 2.8 grade levels (95% confidence interval, 2.6 - 3.0; P < 0.0001). Furthermore, the average readability of the articles exceeded the average reading skill level of U.S. adults (eighth grade) by nearly an entire grade level (95% confidence interval, 0.6-1.0; P < 0.0001). CONCLUSIONS: The majority of the trauma-related articles from the AAOS patient education website have readability levels that may make comprehension difficult for a substantial portion of the patient population.